Structural analysis of lipopolysaccharides from Eikenella corrodens by use of murine monoclonal antibodies. - Kato, T (1989)
The structure of lipopolysaccharides (LPSs) of Eikenella corrodens was analyzed with prepared murine monoclonal antibodies. A common core epitope was found in three of seven LPS preparations from E. corrodens strains and Fusobacterium nucleatum ATCC 25586. Four E. corrodens LPSs were found to possess an O-side-chain epitope which cross-reacted with LPSs from Fusobacterium necrophorum ATCC 25286 and Capnocytophaga ochracea M-12. Lipid A of E. corrodens LPS shared an epitope common among LPSs from various gram-negative rods.